Clinical and genetic analysis of ERCC8-Related cockayne syndrome: hepatic dysfunction as a biomarker, anhidrosis as a rare feature, and rehabilitation outcomes for ankle contractures - Jing Chen; Wei Su; Dan Gao; Fangfang Liu; Shuang Chen; Wenhan Zhang; Min Peng; Tao Lei; Hongmin Zhu (Frontiers in Genetics)
ObjectivesCockayne syndrome (CS), a rare hereditary neurodegenerative disorder caused by pathogenic variants in ERCC6 (CSB) and ERCC8 (CSA), often clinically overlaps with cerebral palsy (CP), leading to misdiagnosis. This study evaluates the role of genetic testing in differential diagnosis, examines hepatic dysfunction as a biomarker of disease severity, and delineates clinical characteristics of CSA-related CS.MethodsA retrospective case series of eight CSA-related CS patients was conducted. Clinical data, neuroimaging, genetic profiles, and hepatic function were analyzed. Disease severity was classified according to established CS subtypes (I–III).ResultsAll patients (6 males, 2 females) presented with early-onset motor delay and spasticity, initially misdiagnosed as CP. Genetic testing identified pathogenic ERCC8 variants, including exon deletions (Exon4; Exon6-12), a nonsense (c.856A>T), frameshift (c.394_398del), and splice-site (c.618-2A>G) variant, confirming autosomal recessive inheritance (compound heterozygous/homozygous). Subtype distribution included CS I (n = 5), CS II (n = 2), and CS III (n = 1). CS II cases exhibited earlier diagnosis and classic CS features. Hepatic dysfunction correlated with disease severity, worsening with progression. Achilles tendon contractures developed in all patients; systematic rehabilitation (n = 5) significantly reduced contracture severity compared to non-rehabilitated cases (n = 3). Two patients displayed anhidrosis, a rarely reported dermatological manifestation.ConclusionGenetic testing is essential to differentiate CSA-related CS from CP. Hepatic dysfunction serves as a biomarker for disease progression, warranting routine monitoring. Rehabilitation therapy mitigates Achilles tendon contractures, underscoring its clinical value. This study expands the phenotypic spectrum of CSA-related CS by identifying anhidrosis as a rarely reported feature, providing insights for diagnosis and management.